2022
DOI: 10.2174/1573397117666211130150241
|View full text |Cite
|
Sign up to set email alerts
|

Functional Disability among Systemic Sclerosis Patients: Relation to Disease Characteristics and Quality of Life Parameters

Abstract: Background: Disability in patients with scleroderma (SSc) has been associated with poor health-related quality of life (HRQoL) in all dimensions, including physical, psychological, and social dimensions. Objective: This study was conducted to examine different factors that may be associated with functional disability and poor HRQoL, with the aim of targeting these factors in the future to improve physical activity, functional outcomes, and HRQoL. Methods: A single-center cross-sectional study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In severe cases of systemic sclerosis (SSc), autologous hematopoietic stem cell transplantation (aHSCT) is superior compared to cyclophosphamide with respect to effect on skin and lung manifestations, survival and quality of life. Nevertheless, major physical and psychological impacts have been found in a first qualitative study by Spierings et al ( 2020) 1 . Objectives: Assessment of subjectively experienced physical and psychological impacts of aHSCT and exploration of potential interrelations of those impacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In severe cases of systemic sclerosis (SSc), autologous hematopoietic stem cell transplantation (aHSCT) is superior compared to cyclophosphamide with respect to effect on skin and lung manifestations, survival and quality of life. Nevertheless, major physical and psychological impacts have been found in a first qualitative study by Spierings et al ( 2020) 1 . Objectives: Assessment of subjectively experienced physical and psychological impacts of aHSCT and exploration of potential interrelations of those impacts.…”
Section: Introductionmentioning
confidence: 99%
“…In the first step, 6 questionnaires were used: Global physical and mental health (SF-36 and Scleroderma Health Assessment Questionnaire = SHAQ), body image (Adapted Satisfaction with Appearance Scale = ASWAP), coping strategies (Freiburger Fragebogen zur Krankheitsverarbeitung = FKV-15), resilience (Resilienzskala = RS-11), and control beliefs (Fragebogen zur Erfassung von Kontrollüberzeugung zu Krankheit und Gesundheit = KKG). In the second step, semi-structured interviews based on Spierings et al ( 2020) 1 were conducted and analysed via mixed methods qualitative content analysis following Mayring (2014). Results: 19 patients (12 female, 7 male, mean age 53.47 years (SD = 9.50)) completed all questionnaires and interviews in a mean time of 6.56 years after aHSCT (SD = 3.90, range 1-12 years).…”
Section: Introductionmentioning
confidence: 99%
“…Depressive symptoms in SSc patients contribute to the worsening of any aspect of the disease [5]. In addition, previous study has reported that depressive symptoms in patients with SSc often have profound impacts on patients' health and wellbeing including increased pain [6][7][8], gastrointestinal involvement [9,10], physical disability [11], impairment of sexual functioning [12], and decreased quality of life [13]. Therefore, depression may be useful targets for interventions aimed at improving subjective health and quality of life in individuals with SSc.…”
Section: Introductionmentioning
confidence: 99%
“…Цю розбіжність можна пояснити чіткими видимими фізичними змінами, пов'язаними з ССД. Ці зміни мають тенденцію погіршуватися з часом, тим самим сприяючи посиленню психологічного дистресу, що проявляється у вигляді посилення симптомів депресії та тривоги [5]. Крім того, часте використання медичних послуг у поєднанні з відповідними зростаючими витратами ще більше ускладнює проблему.…”
unclassified
“…У той час як лікарі можуть надавати пріоритет об'єктивним показникам статусу хвороби, пацієнти часто сприймають інші аспекти свого захворювання як більш тривожні. Ці аспекти охоплюють обмеження рухливості та спритності рук, біль, втома, порушення сну, депресію, сексуальну дисфункцію та емоційні страждання, спричинені дефігуруючими змінами зовнішнього вигляду, такими як пігментними змінами шкірних покривів, контрактури рук і телеангіоектазії обличчя [5]. Всі ці фактори прямо впливають на якість та задоволеність життям.…”
unclassified